Exploring the potential of open innovation for co-creation in entrepreneurship: A systematic literature review - May Portuguez-Castro (Administrative Sciences, 2023)
In recent years, the concept of open innovation has garnered interest among companies due to its potential for generating new models and practices. This study aimed to explore the potential of open innovation for co-creation in entrepreneurship. To achieve this, a systematic literature review (SLR) was conducted, analyzing 53 scientific articles from the Scopus and Web of Science (WOS) databases. The analysis focused on the characteristics related to co-creation and open innovation, the actors involved in these processes, the strategies employed, and the benefits and challenges encountered. The results revealed that: (a) co-creation and open innovation activities enable entrepreneurs to expand their knowledge base through collaboration with diverse stakeholders; (b) the strategies implemented by entrepreneurs have been beneficial in promoting innovation and the creation of shared value, particularly in the development of technologies and new markets; (c) despite recognizing the importance of this collaboration, there are still challenges to be addressed to maximize the advantages of co-creation and open innovation, such as resource scarcity and collaboration skills. Therefore, this study aimed to provide value to entrepreneurs, organizations supporting entrepreneurship, decision-makers, and the community at large in designing programs and mechanisms that foster co-creation and open innovation competencies.
Keywords: 350; co-creation; entrepreneurship; open innovation; systematic literature review; business education; COVID-19